Past, current and future perspectives of housing development and policy in Malaysia - Sufian, Azlinor; Sapian, Abdul Razak (2018)
Irrespective of which category of country, whether developed or developing, housing issues will never end. Malaysia itself has several housing issues, in particular the concept of housing development which began with “sell-then-build” concept where a developer sells houses prior to its construction. Later in 2007, a law was introduced, encouraging developers to embrace the “build–then-sell” concept. Under the concept, a developer collecting only 10% of the selling price from purchasers; and the balance will be settled only upon completion of the houses. The moved from earlier concept of “sell-then-build” to “build-then-sell” was due to the pressure from consumers who were easily exposed to problem of abandonment of project by unscrupulous developers. At present the concept of “sell-then-build” is still allowed under the law, even though the “build-then-sell” concept is becoming more popular, especially for stratified buildings. At the same time a burning issue for consumers is the escalating price of houses which seems to be uncontrollable by the government. Perhaps this issue will be able to be addressed by introducing a new concept called “shell homes” which has already been practiced in other developed countries. This paper aims to examine the present law and policy regulating housing development in Malaysia, the development and the future of this housing law, in relation to the issue of escalating price of houses. It is expected that the concept of “shell homes” will result in a new dimension of law and policy on housing development in Malaysia. Using the qualitative method, this paper evaluates the development of housing law in Malaysia and its future, where it focusses on the new possible concept of “shell homes” as one method of minimizing the cost of houses.